2021
DOI: 10.1155/2021/3614291
|View full text |Cite|
|
Sign up to set email alerts
|

Intelligent Recognition Method of Vehicle Path with Time Window Based on Genetic Algorithm

Abstract: Based on particle filter and improved cuckoo genetic algorithm, an algorithm for intelligent vehicle path recognition with a time window is designed. Particle filter (PF) is an influential visual tracking tool; it relies on the Monte Carlo Chain framework and Bayesian probability, which are essential for intelligent monitoring systems. The algorithm first uses particle filters for visual tracking and then obtains the current operating environment of the vehicle, then performs cluster analysis on customer locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…It was found that previous versions of this submission contained a figure unrelated to the topic of the paper, and this graph was subsequently identified within several other submissions, all with accompanying text claiming to have generated the graph. A number of these submissions were rejected from the journal; however, 6 were published and have now been retracted from Security and Communication Networks and Scientific Programming [2][3][4][5][6].e authors responded to explain that an author from one of the identified submissions had provided copy editing for their manuscript and introduced the graph and accompanying text in error.e authors were unable to provide copies of correspondence to support their claim or the raw data from their study. e authors' explanation did not satisfy the concerns of the editorial board, and the article is therefore being retracted due to concerns with the reliability of the data.e authors do not agree to the retraction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that previous versions of this submission contained a figure unrelated to the topic of the paper, and this graph was subsequently identified within several other submissions, all with accompanying text claiming to have generated the graph. A number of these submissions were rejected from the journal; however, 6 were published and have now been retracted from Security and Communication Networks and Scientific Programming [2][3][4][5][6].e authors responded to explain that an author from one of the identified submissions had provided copy editing for their manuscript and introduced the graph and accompanying text in error.e authors were unable to provide copies of correspondence to support their claim or the raw data from their study. e authors' explanation did not satisfy the concerns of the editorial board, and the article is therefore being retracted due to concerns with the reliability of the data.e authors do not agree to the retraction.…”
mentioning
confidence: 99%
“…It was found that previous versions of this submission contained a figure unrelated to the topic of the paper, and this graph was subsequently identified within several other submissions, all with accompanying text claiming to have generated the graph. A number of these submissions were rejected from the journal; however, 6 were published and have now been retracted from Security and Communication Networks and Scientific Programming [2][3][4][5][6].…”
mentioning
confidence: 99%
“…It was found that previous versions of this submission contained a figure unrelated to the topic of the paper and this graph was subsequently identified within several other submissions, all with accompanying text claiming to have generated the graph. A number of these submissions were rejected from the journal; however, 6 were published and have now been retracted from Security and Communication Networks and Scientific Programming [2][3][4][5][6].e authors responded to explain that an author from one of the identified submissions had provided copy editing for their manuscript and introduced the graph and accompanying text in error.e authors were unable to provide copies of correspondence to support their claim or the raw data from their study. e authors' explanation did not satisfy the concerns of the editorial board, and the article is therefore being retracted due to concerns with the reliability of the data.e authors do not agree to the retraction.…”
mentioning
confidence: 99%
“…It was found that previous versions of this submission contained a figure unrelated to the topic of the paper and this graph was subsequently identified within several other submissions, all with accompanying text claiming to have generated the graph. A number of these submissions were rejected from the journal; however, 6 were published and have now been retracted from Security and Communication Networks and Scientific Programming [2][3][4][5][6].…”
mentioning
confidence: 99%
“…It was found that previous versions of this submission contained a figure unrelated to the topic of the paper and this graph was subsequently identified within several other submissions, all with accompanying text claiming to have generated the graph. A number of these submissions were rejected from the journal; however, 6 were published and have now been retracted from Security and Communication Networks and Scientific Programming [2][3][4][5][6].e authors responded to explain that an author from one of the identified submissions had provided copy editing for their manuscript and introduced the graph and accompanying text in error.e authors were unable to provide copies of correspondence to support their claim or the raw data from their study. e authors' explanation did not satisfy the concerns of the editorial board, and the article is therefore being retracted due to concerns with the reliability of the data.e authors do not agree to the retraction.…”
mentioning
confidence: 99%